Investigation and Analysis of Wall Cracks in Cement Stabilized Rammed Earth Technology - Kandamby, G. W. T. C. (Engineering, Technology & Applied Science Research, 2019)
Cement stabilized rammed earth (CSRE) is one of the developed and affordable housing technologies, adopted in many countries, which has been used in Sri Lanka since 2004 for building single and two-floor houses. Steel slip-form and timber formwork have been used for casting walls. Information collected on wall cracks under these two methods is analyzed to justify the reasons for these cracks. Data collected at the initial stage of construction and its serviceability period of 12 years is considered under this study. Most of the walls have been in satisfactory condition, but few had to be repaired. CSRE wall tends to crack similar to other masonry technology due to faulty construction and environmental changes. Major issues are the cracks due to shrinkage of CSRE material which appeared after one year period of construction. Detailing the construction with the provision of shrinkage cracks is required to mitigate the vertical cracks on CSRE walls.